Pattern and prevalence of metabolic syndrome in obese adolescents aged 10-18 years: a community based study - Jothilakshmi, K.; Vinoth, Vadivel; Kannappan, Suvetha (International Journal of Contemporary Pediatrics, 2020)
Background: The prevalence and magnitude of childhood obesity is increasing in pediatric age group. Incidence of metabolic syndrome is high among obese children and adolescents leading to increased risk of cardiovascular morbidity in long term. For this reason, recognition of metabolic syndrome in obese children is of great importance. Methods: This study was a cross-sectional study carried out among children aged 10-18 years from both urban and rural schools in Coimbatore. Children were screened, sample for metabolic studies collected after consent and analyzed. Results: Total 1582 children in the age group of 10-18 years were screened. 300 children were recruited. Among the studied group, 19.3% were overweight, 30.7% were obese. Metabolic syndrome was present in 55.1% of obese and overweight children. Hyperinsulinemia was present in 30% of obese children. Conclusions: This study done in adolescent school children showed a strong association between obesity and early onset of metabolic syndrome. Early intervention with lifestyle modifications is strongly recommended to prevent long term cardiovascular morbidity.